PENDIDIKAN KARAKTER BERBASIS AL-QUR’AN: Penerapan Pola Sistematika Nuzulnya Wahyu (SNW) di Pondok Pesantren Hidayatullah Panyula Kabupaten Bone - Afifuddin Afifuddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2016)
This article discusses about the pattern of descent of revelation systematics applied in hidayatullah boarding school, Panyula, Bone regency. This research focuses on the implementation of the pattern of descent of revelation systematics in accordance with the qur’anic character building at the boarding school. The researcher collected and analized data by using descriptive qualitative. This research found that hidayatullah boarding school has successfully applied educational methods on quranic based to build students’ character. Based on the descent of revelation systematics, it has regenerated and internalized values as what have been done by the Prophet Muhammad in his first dakwah in Mecca. This research aims to give academic contribution to teachers in order to build Islamic character of the students.